Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2018)
The publication of the last 2018 issue of Studies in Second Language Learning and Teaching marks the end of the eighth year of existence of the journal. It has been a successful year for a number of reasons. First, we have concluded the transition to our electronic platform, which has made the processing of submissions much more manageable. Second, we have published two state-of-the-art special issues, one dedicated to emotions in language learning and the other to language learning strategies. Both of them carry papers by leading scholars in the two respective domains and I am positive that they will contribute to further improvement of the standing of the journal in the field. Third, we have commissioned special issues guest-edited by well-known scholars for several years to come. Fourth, we have seen a major rise in the number of submissions, and, even more importantly, an overall increase in the quality of the manuscripts. Fifth, as can be seen from the indices included in Scopus, the journal continues to have a considerable impact on the field and this impact is very likely to grow in the future. At the same time, there are many problems that we have to face, such as the delays in handling papers caused by the spike in submissions, the need to strike a balance between special issues and regular issues, or the major difficulty in finding suitable reviewers. We are sure, however, that these difficulties are simply challenges that need to be overcome and we are committed to making the journal grow and become even more influential in the field.